Staff’s experiences of implementing patient-initiated brief admission for adolescents from the perspective of epistemic (in)justice - Moberg, Jennie; Schön, Ulla-Karin (Frontiers in Psychiatry, 2022)
Background The implementation of Patient-Initiated Brief Admission (PIBA) in child and adolescent psychiatry (CAP) in Sweden is ongoing. This intervention enables adolescents between the ages of 13–17 and with complex mental health problems to initiate a short care period for relief and support rather than the care apparatus being controlling in this process. Offering it is likely to promote epistemic agency, an exchange of knowledge and recovery from mental health problems. Aim The aim of this study was to explore staff’s perspectives of PIBA for adolescents with complex mental health problems, and what facilitates or hinders its implementation. Methods Twenty seven employees, 21 women and six men, with various professions in CAP were interviewed and the material was analyzed thematically. Results Two overall themes emerged: “Staff’s Experiences of PIBA” and “Managing Clinical PIBA Work.” The results were discussed in relation to the theoretical frameworks of epistemic injustice and Normalization Process Theory (NPT). The main findings indicate that PIBA was generally viewed in a positive way, but that obstacles arose when it was actually put into practice. Findings also point at an overall lack of agency among staff when implementing this new way of working, at the same time as the need to adapt PIBA from an adult psychiatric intervention to one for adolescents in CAP is addressed. Conclusion This article offers insights into the views of psychiatric staff regarding the implementation of PIBA. If staff wish to support epistemic agency and recovery among adolescents, their agency may be an important aspect in the continued implementation. Furthermore, in order for PIBA to become normalized in a sustainable way, we suggest that the continued implementation should be characterized by a youth-friendly framework.